Load shedding strategy based on a simple method to mitigate fault-induced delayed voltage recovery (Publicaciones en Ciencias y Tecnología, 2022)
FIDVR represents a major threat to the safe and reliable operation of electrical power systems with load dominated induction motors. In this paper, a load shedding strategy based on the critical recovery time (CRT) of voltage is proposed to mitigate FIDVR. The CRT allows identify the most effective load mainly responsible for the FIDVR, while the CRT desviation determines the amount of load to be disconnected in each effective bus according to the severity of the FIDVR. The results obtained by simulating the strategy in the Power Factory DigSilent DPL on the 39 Bus New England system showed that it is capable of identifying the most effective location and amount of load to mitigate FIDVR. Compared with the conventional UVLS scheme, the proposed strategy achieves a fast voltage recovery and requires a smaller amount of load to be disconnected. It is concluded that the proposed load shedding strategy responds adaptively to the severity of the FIDVR to disconnect the minimum amount of load in order to improve short-term voltage stability.
Keywords: FIDVR; load shedding; short term voltage instability; induction motor